GUT LOAD, TRANSIT TIME AND TURNOVER OF CLAY LOAM SOIL AND PRESSMUD BY TROPICAL EARTHWORMS - PARTHASARATHI, K (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
Gut load, transit time and tumover (cast production) of substrato-clay loam soil (S) and pressmud (PM) in Eisenia fetida, Perionyx excavatus, Lampito mauriti and Eadinimus eugeniae have been determined. The mean dry weight of gut load (S and PM) in E fetidia was 323.36 and 448.08, P. excavatus 369.22 and 490.82, L. mauritii 786.63 and 868.36 and E eugeniae 903.72 and 1063.26 mg day, respectively. The gut transit time for one filling of S and PM was about 5 and 3,7 and 48 and 6, and 10 and 7 hours, respectively. The mean dry weight of cast laid by each worm was about 266 23 and 394.10.352.07 and 464.26, 785.47 and 993.27 and 906.72 and 1157.18 mg/day, respectively. E eugeniae show more substrates load, easy and shorter transit time and more cast production over other species of worms because of its greater size and voracious feeding habit. The gut load, transit time and turmower of PM was earlier and more by each species of worms over S, due to its rich nutrient contents and lesser particle size.